Mediating Role of Information Flow in Enhancing Nursing Service Quality and Patient Satisfaction - Huang, Ying; Ali, Dhakir Abbas; Wang, Shuangshuang; Zhang, Rongmei (Ital Publication, 2025)
Patient satisfaction is a key factor in the success of hospitals worldwide, making it an important focus for contemporary research. This study aims to examine the impact of service quality, employee satisfaction, and the organizational environment on patient satisfaction in Chinese hospitals. Additionally, it investigates the mediating role of information flow in the relationships between service quality, employee satisfaction, the organizational environment, and patient satisfaction in Chinese hospitals. Data for the study was collected through survey questionnaires administered to patients in government hospitals in China. The reliability of the data and the relationships among the constructs were analyzed using Smart-PLS software. The findings revealed that service quality, employee satisfaction, and the organizational environment positively influence patient satisfaction in Chinese hospitals. Moreover, the results indicated that information flow significantly mediates the relationships between service quality, employee satisfaction, the organizational environment, and patient satisfaction. These findings provide valuable insights for policymakers, offering guidance on strategies to enhance patient satisfaction by focusing on improving service quality, ensuring effective information flow, and fostering a positive organizational environment. Doi: 10.28991/ESJ-2025-09-01-09 Full Text: PDF